The relationship between different iodine sources and nutrition in pregnant women and adults - Sun, Rong; Fan, Lijun; Du, Yang; Liu, Lanchun; Qian, Tingting; Zhao, Meng; Che, Wenjing; Liu, Peng; Sun, Dianjun (Frontiers in Endocrinology, 2022)
Background Different iodine supplement measures emerge along with the economy development in China. The article objectives are to compare and explore the relationship between iodine sources and nutrition of pregnant women and adults. Methods 2145 pregnant women and 1660 adults were investigated by multi-stage random method. Questionnaire was used to collect basic information and the consumption of food, water and iodine preparations. Household salt, individual urine and blood samples were collected, and thyroid function and morphology of pregnant women were measured. Results The median urinary iodine concentration (MUIC) of pregnant women (164.49 μg/L) was lower than adults (187.30 μg/L, p < 0.05). Iodine supplement with IS (Iodized Salt) was the main measure for pregnant women and adults, and the difference was mainly on the consumption of iodine preparations between pregnant women (5.19 %) and adults (0.85 %). Moreover, adults' dietary iodine intake from food (100.6 μg/d), iodized salt (140.8 μg/d) and drinking water (6.0 μg/d) were higher than those of pregnant women (86.5 μg/d, 107.2 μg/d and 3.5 μg/d, respectively). Compared with iodine supplement with IS, ISFP (Iodized Salt + iodine-rich Food + iodine Preparations) could reduce the risk of iodine deficiency for pregnant women. The MUICs for pregnant women and adults of iodine supplements with IF (Iodine-rich Food) and ISF (Iodized salt + iodine-rich Food) were lower. For pregnant women, thyroid nodule (11.90 %) and peroxidase antibody (TPOAb) positive (9.32 %) were high prevalent thyroid diseases, and habitation (urban/rural), gestation, annual income, drinking water type would affect them. Conclusion Pregnant women and adults had adequate iodine nutrition in four provinces. The iodine supplement measures of them were different, the consumption of iodine preparations in pregnant women was higher, and their dietary iodine intake was lower than adults. ISFP was an effect measure for pregnant women to supplement iodine.